2020
DOI: 10.3390/molecules25173926
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Properties of Green Tea (Camellia sinensis) in Parkinson’s Disease: A Review

Abstract: Neurodegenerative disease is a collective term given for the clinical condition, which results in progressive degeneration of neurons and the loss of functions associated with the affected brain region. Apart from the increase in age, neurodegenerative diseases are also partly affected by diet and lifestyle practices. Parkinson’s disease (PD) is a slow onset neurodegenerative disorder and the second most common neurodegenerative disease, which affects the motor system. Although there is no prescribed treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 150 publications
0
27
0
2
Order By: Relevance
“…PD is the second most common neurodegenerative disease worldwide being characterized by a progressive degeneration of nigrostriatal dopaminergic neurons [ 39 , 40 ]. Currently, the molecular mechanisms underlying the loss of these neurons still remain vague; however, mitochondrial dysfunction, apoptosis, and neuroinflammation are thought to play an important role in dopaminergic neurotoxicity in PD [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…PD is the second most common neurodegenerative disease worldwide being characterized by a progressive degeneration of nigrostriatal dopaminergic neurons [ 39 , 40 ]. Currently, the molecular mechanisms underlying the loss of these neurons still remain vague; however, mitochondrial dysfunction, apoptosis, and neuroinflammation are thought to play an important role in dopaminergic neurotoxicity in PD [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…No cure exists for NDDs, particularly in advanced stages. The drugs that are approved by the FDA, such as acetylcholine esterase inhibitors (donepezil, rivastigmine) as well as levodopa for PD, which crosses the blood–brain barrier and restores dopamine levels in the substantia nigra, only ameliorate the symptoms and slow the progression of the diseases for several years [ 1 ]. Newer therapy approaches that are focused on neuroregeneration, i.e., structural and functional recovery of the damaged nervous system through immunomodulation, inhibition of formation of protein aggregates, disaggregation of misfolded proteins, and induction of autophagy, give hope that the degeneration process of afflicted neurons might be slowed and the recovery rates and longevity improved [ 222 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative diseases is a collective term for the clinical conditions characterized by gradual and progressive severe damage to neuronal cells, particularly in the central nervous system (CNS), which results in the loss of functions that are associated with the affected brain region [ 1 , 2 ]. Different in etiology and clinical symptomatology, NDDs share some common features at the cellular and molecular levels, such as protein misfolding, aggregation, and deposition; mitochondrial disfunction; chronic inflammation; and, oxidative damage of biomolecules, including lipids, proteins, and DNA ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The brain requires comparably high amount of oxygen [ 51 ] and the impaired oxidative balance in the brain has been substantially determined as the common feature of neurodegenerative diseases [ 52 , 53 ]. Mounting research have reported the utilization of natural polyphenols on neurodegenerative diseases due to their antioxidant and anti-aging properties [ 54 , 55 , 56 , 57 , 58 ]. Grape is an evident example of fruits that contain a high content of polyphenols [ 59 ].…”
Section: Anti-aging Effects Of Polyphenolsmentioning
confidence: 99%